A cross-neutralizing antibody between HIV-1 and influenza virus. - Chang-Chun D Lee; Yasunori Watanabe; Nicholas C Wu; Julianna Han; Sonu Kumar; Tossapol Pholcharee; Gemma E Seabright; Joel D Allen; Chih-Wei Lin; Ji-Rong Yang; Ming-Tsan Liu; Chung-Yi Wu; et al. (PLoS Pathogens)
Incessant antigenic evolution enables the persistence and spread of influenza virus in the human population. As the principal target of the immune response, the hemagglutinin (HA) surface antigen on influenza viruses continuously acquires and replaces N-linked glycosylation sites to shield immunogenic protein epitopes using host-derived glycans. Anti-glycan antibodies, such as 2G12, target the HIV-1 envelope protein (Env), which is even more extensively glycosylated and contains under-processed oligomannose-type clusters on its dense glycan shield. Here, we illustrate that 2G12 can also neutralize human seasonal influenza A H3N2 viruses that have evolved to present similar oligomannose-type clusters on their HAs from around 20 years after the 1968 pandemic. Using structural biology and mass spectrometric approaches, we find that two N-glycosylation sites close to the receptor binding site (RBS) on influenza hemagglutinin represent the oligomannose cluster recognized by 2G12. One of these glycan sites is highly conserved in all human H3N2 strains and the other emerged during virus evolution. These two N-glycosylation sites have also become crucial for fitness of recent H3N2 strains. These findings shed light on the evolution of the glycan shield on influenza virus and suggest 2G12-like antibodies can potentially act as broad neutralizers to target human enveloped viruses.